THE EXPLORATION OF PRE-SERVICE EFL TEACHERS’ CHALLENGES IN FIELD PRACTICUM - Pasaka, Rainal Wempi; Emilia, Emi; Amalia, Lulu Laela (International Journal of Education, 2014)
This study investigates the challenges that six pre-service EFL teachers of a Bachelor ofEducation (Sarjana Pendidikan) program experienced in conducting field practicum. This studyemploys a qualitative research design, with a phenomenological approach. Data was gatheredthrough in-depth interviews. The interview data was then scrutinized and codified, respectiveto emergent themes through thematic analysis procedures (Merriam, 1988 in Emilia, 2007,p. 84). The findings showed that the pre-service teachers experienced challenges related tolesson preparation, classroom management, and communication breakdown within their fieldpracticum. The study concludes with a recommendation and justification for teacher preparationprograms to provide pre-service teachers with: robust theoretical frameworks in order to designinstruction; practical experience in classroom management; profound knowledge of Englishlanguage; and activities that develop strong confidence in teaching. In addition, teacherpreparation programs are endorsed to formally inform mentor teachers regarding their rolesand responsibilities in the practicum.Keywords: Pre-service teachers, teacher preparation programs, field practicum